2013
DOI: 10.3329/bjmed.v24i1.15030
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Suicide and Para Suicide in Rural Bangladesh

Abstract: Bangladesh Journal of Medicine, Vol 24 No 1, 2013, Page 14-19 DOI: http://dx.doi.org/10.3329/bjmed.v24i1.15030

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…16 The male-female ratio is slightly inclined towards the females was possible due to passive gender role, early marriage, lack of economic freedom, low literacy and such cultural factors predominant in the Asian countries. 16,24,25 The rural people attempted suicide most in the current study (73%) and this was similar to other studies in perspective of Bangladesh. 16,17,18,25 Unmarried subjects were also found to be slightly more than married (51%) which could be explained by the study from Denmark which reported cohabiting or single marital status was a significant risk factor for suicide.…”
Section: Suicide Was One Of the Priority Conditions In The Who Mentalsupporting
confidence: 91%
See 2 more Smart Citations
“…16 The male-female ratio is slightly inclined towards the females was possible due to passive gender role, early marriage, lack of economic freedom, low literacy and such cultural factors predominant in the Asian countries. 16,24,25 The rural people attempted suicide most in the current study (73%) and this was similar to other studies in perspective of Bangladesh. 16,17,18,25 Unmarried subjects were also found to be slightly more than married (51%) which could be explained by the study from Denmark which reported cohabiting or single marital status was a significant risk factor for suicide.…”
Section: Suicide Was One Of the Priority Conditions In The Who Mentalsupporting
confidence: 91%
“…16,24,25 The rural people attempted suicide most in the current study (73%) and this was similar to other studies in perspective of Bangladesh. 16,17,18,25 Unmarried subjects were also found to be slightly more than married (51%) which could be explained by the study from Denmark which reported cohabiting or single marital status was a significant risk factor for suicide. 26 Being separated or divorced was noted to be significantly associated with a suicidal act in another study.…”
Section: Suicide Was One Of the Priority Conditions In The Who Mentalsupporting
confidence: 91%
See 1 more Smart Citation
“…5 Studies also found that married females living in low socioeconomic status in the country are dying by suicide more frequently, although the difference was not prominent in the current study. 5,6 The total population structure is also comparable with the study sample, as the most recent census revealed a nearly equal number of men and women, and >60% of the population were aged <30 years. However, our findings revealed that marriage by choice was more common among the suicide cases, which was statistically significant.…”
Section: Discussionsupporting
confidence: 51%
“…5 Female gender, age <30 years and immediate emotionally charged events, rather than mental disorders, have been reported as risk factors in the country. 5,6 As a result, few and sporadic suicide prevention activities have been initiated, with no central strategy or harmonisation. 7 With this background, there is an immediate and unmet need to determine the risk factors for suicide in Bangladesh, to formulate a national suicide prevention strategy.…”
mentioning
confidence: 99%